Overexpression of the HECT ubiquitin ligase PfUT prolongs the intraerythrocytic cycle and reduces invasion efficiency of Plasmodium falciparum - Jankowska-Döllken, Monika; Sanchez, Cecilia P.; Cyrklaff, Marek; Lanzer, Michael (Scientific reports, 2019)
The glms ribozyme system has been used as an amenable tool to conditionally control expression of genes of interest. It is generally assumed that insertion of the ribozyme sequence does not affect expression of the targeted gene in the absence of the inducer glucosamine-6-phosphate, although experimental support for this assumption is scarce. Here, we report the unexpected finding that integration of the glms ribozyme sequence in the 3′ untranslated region of a gene encoding a HECT E3 ubiquitin ligase, termed Plasmodium falciparum ubiquitin transferase (PfUT), increased steady state RNA and protein levels 2.5-fold in the human malaria parasite P. falciparum. Overexpression of pfut resulted in an S/M phase-associated lengthening of the parasite’s intraerythrocytic developmental cycle and a reduced merozoite invasion efficiency. The addition of glucosamine partially restored the wild type phenotype. Our study suggests a role of PfUT in controlling cell cycle progression and merozoite invasion. Our study further raises awareness regarding unexpected effects on gene expression when inserting the glms ribozyme sequence into a gene locus.
Gesehen am 09.01.2020